Uruguay - Equality of Opportunity : Achievements and Challenges - World Bank (World Bank, 2012)
The report is organized around the main achievements and challenges Uruguay faces from the perspective of expanding opportunities for children in the XXI century, a perspective that is consistent with the country's stated social welfare goals and upper middle-income status. Chapter two presents the main achievements and challenges faced at the national level in access to opportunities for key goods and services: education, health, housing and infrastructure, and information and communications technology. It also presents results over time using limited comparable data. Chapter three explores the geographic distribution of the Human Opportunity Index (HOI) in depth as well as the distribution of gains and losses over time. Both chapters measure opportunities to access a basic set of goods and services and an expanded set more consistent with Uruguay's relative development, whenever data allows. This report also offers some policy applications of the equality of opportunity framework as well as policy considerations to support an opportunity-enhancing environment. Chapter four provides an assessment of how recent education, social, and technological programs may fare from the perspective of expanding opportunities to children. Chapter five concludes.